Men and Natural Resources in the Territory of Seprio during Middle Ages. The Case of Velate between 11th and 12th Centuries (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The paper proposes a reconstruction of the history of the uncultivated lands in the area of ​​Velate (Varese) in the Middle Ages and it claims, on the basis of historical and archaeological evidence, that there is a strong continuity between the medieval landscape and the current one. This is due first to the struggle of rural communities to preserve the public exploitation of uncultivated lands, then to the inclusion of the area in the territory of the "sacro monte".
Keywords: Woods; Medieval Landscape; Velate